KOMPARASI BOBOT POTONG, BOBOT KARKAS DAN PERSENTASE KARKAS PADA SAPI RANCAH DAN PERANAKAN ONGOLE BERDASARKAN MUTASI PADA GEN LEPTIN - Nena Hilmia; Dedi Rahmat; Primiani Edianingsih; Yurleni Faisal (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2022)
Weight and percentage of the carcass are very important in beef cattle production because they are economic parameters, which describe the number of parts that can be consumed. This study aimed to determine the effect of mutations in R25C and R25H in the Leptin gene on slaughter weight, carcass weight, and carcass percentage of Rancah and Ongole Grade cattle. The secondary data used were 4 genotypes in Rancah cattle, namely CC, CT, CA, and TT respectively, 6, 2, 4, and 2 heads, and 3 genotypes in Ongole Grade cattle, namely CC, CT, and CA, respectively. 4, 2, and 1 head. The data on slaughter weight, carcass weight, and carcass percentage were 14 males of Rancah cattle aged 1.5 – 2.5 years, while data for PO cattle were obtained from 7 males of Ongole Grade 1.5 years old. Parameters measured were slaughter weight, carcass weight, carcass percentage. Data were analyzed descriptively. The results showed that genetic diversity in Rancah and PO cattle due to the R25C and R25H mutations in the Leptin gene was not differences in slaughter weight, carcass weight, and carcass percentage.